Co-factor independent oxidases ncnN and actVA-3 are involved in the dimerization of benzoisochromanequinone antibiotics in naphthocyclinone and actinorhodin biosynthesis - Baral Bikash; Matroodi Soheila; Siitonen Vilja; Thapa Keshav; Akhgari Amir; Yamada Keith; Nuutila Aleksi; Metsä-Ketelä Mikko (Oxford University Press, 2025)
Streptomyces produce complex bioactive secondary metabolites with remarkable chemical diversity. Benzoisochromanequinone polyketides actinorhodin and naphthocyclinone are formed through dimerization of half-molecules via single or double carbon-carbon bonds, respectively. Here we sequenced the genome of S. arenae DSM40737 to identify the naphthocyclinone gene cluster and established heterologous production in S. albus J1074 by utilizing direct cluster capture techniques. Comparative sequence analysis uncovered ncnN and ncnM gene products as putative enzymes responsible for dimerization. Inactivation of ncnN that is homologous to atypical co-factor independent oxidases resulted in the accumulation of fogacin, which is likely a reduced shunt product of the true substrate for naphthocyclinone dimerization. In agreement, inactivation of the homologous actVA-3 in S. coelicolor M145 also led to significantly reduced production of actinorhodin. Previous work has identified the NAD(P)H-dependent reductase ActVA-4 as the key enzyme in actinorhodin dimerization, but surprisingly inactivation of the homologous ncnM did not abolish naphthocyclinone formation and the mutation may have been complemented by an endogenous gene product. Our data suggests that dimerization of benzoisochromanequinone polyketides require two-component reductase-oxidase systems.